STUDY INTO DEPENDENCE OF CAVITATION ACTIVITY ON LIQUID TEMPERATURE - A. V. Kotukhov; A. V. Krasovskiy; V. V. Shaplyka; N. V. Dezhkunov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Cavitation activity in non-homogeneous ultrasonic field have been studied. It has been shown that the character of temperature dependencies of cavitation activity is different for different points of the field. For example, cavitation activity at the surface of the radiator and at the liquid - gas surface decreases with temperature. There are points in the volume of the liquid where temperature dependencies are curves with maximum, i.e. it grows with temperature, achieves maximal value and then decreases.